Sin and Punishment: The Ethics of Divine Justice and Retribution in Ancient Near Eastern and Old Testament Texts - Berlejung, Angelika (Interpretation, 2015)
This article gives a short survey of concepts of “sin and sanction,” the “crisis of Wisdom,” and divine justice in ancient Mesopotamian texts and in the Old Testament. A concluding summary provides a comparison of these two ancient Near Eastern cultures’ understandings of the ethics of divine justice.